IMPLEMENTASI PENDIDIKANKESEHATAN SEBAGAI SEBUAH UPAYA UNTUK MENINGKATKAN PENGETAHUAN DAN PERILAKU IBU DALAM MEMBERIKAN ASI EKSKLUSIF - Kurniawati, Dini (Jurnal Pengembangan Pendidikan, 2012)
Abstract. In general practice of giving exclusive breast-feeding still low fromachievement target although various studies have shows the benefit of exclusivebreast-feeding to the baby’s health have been done. To achieve this, there needs to be knowledge for mothers about exclusive breast-feeding because mother’s knowledge is very important domain in shaping thebehavior of giving exclusivebreast-feeding. The purpose of this study was to know the influence of healtheducation on mother’s knowledge and behavior in giving exclusive breast-feeding.Study Design is one pretest posttest designs. Techniques used in taking samplesis purposive sampling with a sample size of 30 people. Based o the result ofdata analysis with sign test techniques is obtained p-value /Asym sig =0,000< α (0,05) so it can be concluded that there is influence between health education on mother’s knowledge andbehavior in giving exclusive breast-feeding. To improve the achievement ofgiving exclusive breast-feeding, they need to have adequate health educationand to increase knowledge. Patient’s knowledge about exclusive breast-feedingwill shape mother’s attitudes to do exclusive breast-feeding. In theory,changes in behavior or adopt new behaviors, follow the steps mentioned above,are through the process: knowledge,attitude,practice. Key words: health education, knowledge, behavior,exclusive breast-feeding